FINANCIAL ASPECTS OF ECOLOGICAL CLEAN LEASE IN CARPATHIAN MACROREGION - Sus. T.Yо. (The actual problems of regional economy development, 2016)
The features of the modern development of the agricultural land lease market in Ukraine are considered. The possible two scenarios of development of land relations in the context of the moratorium on land sales and financial crisis are proposed. The basic directions of development of land relations and the threat of sale of agricultural land bypass the moratorium by perpetual lease transaction are considered. Because of the difficult economic conditions in Ukraine, devaluation of the national currency and decreasing of real rent, increasing poverty among the rural population perpetual lease agreements will gain more and more popularity. This creates dangerous tendencies for legal land quasi market organization in terms of the moratorium and in modern realities it is gaining popularity among large agricultural holdings. The increasing popularity of perpetual lease promotes the factor that land owners are able to obtain a large sum of money immediately after contract conclusion, but not in parts during the lease term. Inducing factors of such a scenario of land relations development and the gaps in legal support of agricultural reform are considered. Financial problems of ecological clean land lease and the ways of their solution are outlined. JEL: Q 14, R 58